An endemic and endangered new species of the lizard liolaemus montanus group from southwestern peru (Iguania: Liolaemidae), with a key for the species of the l. reichei clade - Quiroz, Aarón J. (2021)
The southwestern Andes of Peru harbor a hidden taxonomic diversity of reptiles. We describe a new species of Liolaemus Wiegmann (Iguania: Liolaemidae) from xerophytic environments of the southwestern slopes of the Andes of Peru, 2,400– 2,900 m asl. The new species, previously considered to be a population of L. insolitus Cei, exhibits unique diagnostic characters of morphology, scalation and color pattern, and molecular evidence that suggest that it belongs in the Liolaemus montanus species group and the L. reichei clade. Moreover, the species is endemic to the eastern slopes of La Caldera batholith in the Department of Arequipa, southern Peru. We also provide information on the conservation status of the species and suggest it be included in the IUCN red list of the threatened species as endangered (EN). A key for the species of the L. reichei clade is provided.